Simulasi Laju Aliran Udara pada Mesin Oven Pengering Kerupuk dengan Burner Sederhana Berbasis Computational Fluid Dynamics - Syahrul Mahfudli Rohman; Agus Mukhtar; Aan Burhanudin (CV. IRA PUBLISHING, 2024)
Drying is the process of removing water or separating a relatively small amount of water from a material using heat energy. One method of drying is through oven processing, which aims to reduce the moisture content in materials using an oven. This study aims to analyze the airflow rate in an oven using Computational Fluid Dynamics (CFD) simulation and to examine the effect of temperature variations on airflow rate using CFD simulation. The research method employed is experimental, with data collection techniques including descriptive analysis, involving experiments, simulation results, and documentation. The study found that the simulated airflow rate using Ansys R2 2020 varied with different temperatures. At 70℃, the air velocity ranged from 1.108 m/s to 4.432 m/s, while at 75℃, it ranged from 1.882 m/s to 11.29 m/s. Turbulence occurred at both temperatures, and higher temperatures resulted in faster airflow rates due to reduced air resistance. At 75℃, the crackers achieved optimal dryness, with a weight reduction of 95%. High temperatures can reduce air density which can increase air flow speed due to a decrease in resistance experienced by the air.